Caregiving Stress among Caregivers of Patients admitted with Suicidal Attempt - Thapa, Prekshya; Lama, Sami; Pradhan, Nirmala; Thapa, Kriti; Kumar, Rajesh; Basnet, Madhur (Journal of Nepal Health Research Council, 2021)
Background: Family caregivers play a key role in preventing suicide attempts. The objective of this study was to study the caregiving stress of the patients admitted with suicide attempt at a tertiary care hospital in Nepal. Methods: A mixed method study was conducted with 52 family caregivers of suicidal people who had been admitted at B. P. Koirala Institute of Health Sciences, Dharan with history of suicide attempt. Data were collected through interview using Kingston Caregiver Stress Scale and in-depth interview was conducted on five family caregivers using interview framework developed in the department for the purpose. Results: The mean caregiving stress score was 29.84(SD=5.11), with the mean score of score 22.0 (±3.9) in caregiving issues, 4.3(±1.9) in family issues and 3.5(±0.9) in financial issues respectively. Majority (65.4%) of the caregiver had perceived stress scores above the mean score. Caregiver’s stress was significantly associated with age (p= 0.023), marital status (p= 0.008) and patient’s mode of attempt (p=0.035) with stress level being higher in those with older age, married and hanging as the mode of suicide attempt. In-depth interview showed that financial difficulties, emotional and physical problems, difficulty maintaining daily activities, and stigma related problem seem to significantly increase caregiver’s stress. Conclusions: The study showed overall stress level of caregivers was high. Keywords: Caregiver; stress; suicide attempter